2015
DOI: 10.1146/annurev-genet-112414-054823
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of the Host Tropism of Human-Tropic Pathogens

Abstract: Infectious diseases are the second leading cause of death worldwide. Although the host multitropism of some pathogens has rendered their manipulation possible in animal models, the human-restricted tropism of numerous viruses, bacteria, fungi, and parasites has seriously hampered our understanding of these pathogens. Hence, uncovering the genetic basis underlying the narrow tropism of such pathogens is critical for understanding their mechanisms of infection and pathogenesis. Moreover, such genetic dissection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 168 publications
0
45
0
Order By: Relevance
“…The host range or specificity of a virus is often limited due to several reasons, such as the lack of host factors the virus depends on or the incompatibility of these factors’ orthologs in different species. Alternatively, but not necessarily mutually exclusive, the ability to evade the antiviral immune response of a given host can also shape the species tropism of viruses (Ding et al, 2018; Douam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host range or specificity of a virus is often limited due to several reasons, such as the lack of host factors the virus depends on or the incompatibility of these factors’ orthologs in different species. Alternatively, but not necessarily mutually exclusive, the ability to evade the antiviral immune response of a given host can also shape the species tropism of viruses (Ding et al, 2018; Douam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Following binding of ACE2, the S protein is subsequently cleaved by the host transmembrane serine protease 2 (TMPRSS2) to release the spike fusion peptide, promoting virus entry into target cells (Hoffmann et al, 2020; Wan et al, 2020). It has been repeatedly demonstrated that the interaction of a virus with (a) species-specific receptor(s) is a primary determinant of host tropism and therefore constitutes a major interspecies barrier at the level of viral entry (Douam et al, 2015). For example, murine ACE2 does not efficiently bind the SARS-CoV or SARS-CoV-2 S protein, hindering viral entry into murine cells; consequently, a human ACE2 transgenic mouse was developed as an in vivo model to study the infection and pathogenesis of these two viruses (Bao et al, 2020; Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A nonsusceptible or nonpermissive species may not possess the appropriate molecular factors or may have incompatible orthologs of factors needed for successful infection, such as receptors for a specific virus to enter host cells. Additionally, dominant restriction factors may actively interfere with one or more steps of a virus' life cycle (44). Alternatively, but not necessarily mutually exclusive, the varying abilities of a pathogen to evade and disrupt the immune response of a given host can also shape species tropism.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the most deadly and common pathogens to mankind display species specificity and can only infect humans or closely related nonhuman primates (1). Other human pathogens have the ability to infect a broader range of species, yet these infections do not faithfully recapitulate human disease.…”
Section: Introductionmentioning
confidence: 99%